2016
DOI: 10.1177/1545968316675428
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Foot Placement Asymmetries and Metabolic Cost of Transport in Hemiparetic Gait

Abstract: Stroke survivors often have a slow, asymmetric walking pattern. They also walk with a higher metabolic cost than healthy, age-matched controls. It is often assumed that spatial-temporal asymmetries contribute to the increased metabolic cost of walking post-stroke. However, elucidating this relationship is made challenging due to the interdependence between spatial-temporal asymmetries, walking speed, and metabolic cost. Here, we address these potential confounds by measuring speed-dependent changes in metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 48 publications
8
80
0
1
Order By: Relevance
“…Two of these studies, in particular, suggested that increased gait asymmetry in people post-stroke is correlated with the increased metabolic cost of walking Farris et al, 2015). There is thus great interest in the development of post-stroke gait interventions that can reduce the metabolic cost of walking by inducing more symmetrical walking (Finley and Bastian, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two of these studies, in particular, suggested that increased gait asymmetry in people post-stroke is correlated with the increased metabolic cost of walking Farris et al, 2015). There is thus great interest in the development of post-stroke gait interventions that can reduce the metabolic cost of walking by inducing more symmetrical walking (Finley and Bastian, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the physical realism of each musculoskeletal modeling approach/metabolic cost model combination, we identified five experimental trends in the literature for how CoT varies with other quantities for individuals post-stroke. The first three quantities were step position asymmetry, stance time asymmetry, and double-support time asymmetry that were reported to increase as the cost of transport increased (Finley and Bastian, 2017). Inversely, the two other quantities were speed and Fugl-Meyer score that were observed to decrease as the cost of transport increased.…”
Section: Discussionmentioning
confidence: 97%
“…To evaluate the physical realism of different metabolic cost modeling methods, we compared metabolic cost estimates to trends reported in the literature. For individuals post-stroke, Finley and Bastian (Finley and Bastian, 2017) reported a decrease in metabolic cost as walking speed increased and severity of motor impairment decreased. In contrast, for the same subject population, Finley and colleagues (Finley et al, 2015;Finley and Bastian, 2017) also reported that metabolic cost increased as differences in step position, stance time, and double support time increased.…”
Section: Model Personalization Affects Metabolic Cost?mentioning
confidence: 99%
See 1 more Smart Citation
“…Poststroke changes in lower extremity function lead to persistent biomechanical abnormalities during walking including but not limited to decreased paretic stance time 3 , and asymmetric step lengths [4][5][6][7] . Previous research has shown positive associations between spatiotemporal asymmetries and the metabolic cost of walking [8][9][10] , and in people post-stroke, this increased cost may be due in part to sub-optimal coordination of leading limb contact and trailing limb push-off forces 10,11 . Therefore, it is possible that reducing asymmetry may reduce the metabolic burden of walking post-stroke.…”
Section: Introductionmentioning
confidence: 98%